Ecualizando los Márgenes: Cultura Expresiva y Renovación Urbana en un Barrio Histórico del Centro de Lisboa - Sánchez Fuarros, Iñigo (Trabalhos de Antropologia e Etnologia, 2020)
This article explores the link between contemporary urban revitalization programs and the enactment of the past for the creation of new urban images for tourism consumption. Drawing on fieldwork research in Lisbon’s Mouraria quarter, I discuss the significance of music as a lever for the renewal and marketing of this infamous inner-city neighborhood. In particular, I focus on the restitution of fado, Portugal’s national song, to the neighborhood public and semi-public spaces and this popular genre of urban song has been instrumentalised as a new identity marker of the territory.